Model Identifikasi Risiko Dan Perhitungan Nilai Tambah Pada Rantai Pasokan Janggelan (Studi Kasus Pada CV. Bumi Makmur) - MURTI, WIKKY SASANA; , HAFIDH MUNAWIR, ST., M.Eng (2016)
As a region which has fertile soil, Wonogiri could be a growing area by improving the living conditions of the population. To achieve this, the need for the movement to utilize and manage existing resources well. Natural resources that thrives in Wonogiri one of which is a provisional / Cincau (Mezona Palustris). The planting area in 2010 reached approximately 1,348 ha with a production level of dry tentative reached 5.323 tons / year. Disruption of the supply chain process resulted in disruption of raw material processing provisional that can harm each chain. Methods HOR (House of Risk) is a method to proactively manage risk, where risk agents were identified as the cause of event risk can be managed by giving the order based on the magnitude of potential impacts. It should also apply the concept of added value generated by each chain tentative. Hayami method of analysis of value-added processing of agricultural products can be done in a simple way, that is through the calculation of value added per kilogram of raw materials for processing one that produces a particular product. From the calculation and the calculation of value added ARP (aggregate risk potential) on farmers by Rp4.567,00 / kg, the ratio of added value by 63%, and the cumulative results of the risk by 23%; the chain of collectors of Rp661,00 / kg, the ratio of value-added 8%, and the cumulative results of the risk by 16%; the chain of manufacturers of Rp10.553,00 / kg, added value ratio of 35%, and the cumulative value of the risk by 23%; chain cookers for Rp3.373,00 / kg, added value ratio of 14%, and the cumulative results of the risk by 16%; and the chain of sellers of Rp1.989,00 / kg, added value ratio of 10%, and the cumulative results of the risk by 10%. On the results of the calculation of the added value obtained by the largest value-added chain of farmers with an added value of Rp4.567,00 / kg, added value ratio of 63%. At the risk weighting obtained the greatest risks derived from the chain manufacturer with a cumulative value of 35%. Keywords: Supply Chain, HOR, Supply Chain Risk Management, Value Added